Die "bekentenisse van die vlees" in die sentrale Middeleeue: "n Verruiming van Foucault se lesing in Histoire de la sexualité 1 (La volonté de savoir) - Beukes, Johann (HTS teologiese studies, 2022)
The ‘confessions of the flesh’ in the central Middle Ages: An expansion of Foucault’s reading in Histoire de la sexualité 1 (La volonté de savoir). This article expands Michel Foucault’s (1926–1984) reading of the ‘confessions of the flesh’ in handbooks of penance written during the central Middle Ages in the first volume La volonté de savoir of his (current) four-volume series Histoire de la sexualité. After the posthumous publication of the fourth volume Les aveux de la chair (2018), in which Foucault takes his analysis of the historical foundations of confessional practices in the late 12th century to the first half of the 14th century even further back, to the ‘confessions of the flesh’ in the patristics of the 3rd to the 5th centuries, it has become sensible to illuminate Foucault’s condensed reading of confessional scripts in La volonté de savoir itself. This exposition pertinently applies to Foucault’s correct conclusion that sex was prioritised above all other ‘sins’, ‘vices’, and ‘transgressions’ in central Medieval confessional scripts; therefore, as he famously noted, becoming a ‘seismograph of subjectivity in Christian cultures’. Against this backdrop, it is considered how thinkers from the central Middle Ages themselves reflected on the sacramentalisation of confession after the Fourth Lateran Council of 1215 – since Foucault himself did not substantially elaborate on it. The reflections of three philosophers from the central Middle Ages on the relation between sex, confession and absolution are subsequently presented as an expansion of Foucault’s reading in La volonté de savoir. Firstly, Alan of Lille’s (d.1203) interpretation of the Summae confessorum in his Liber poenitentialis is revisited, concluding that Lille’s perspective was ‘hermeneutical’, in terms of his insistence that the confessor should adjust his interrogations according to seven Aristotelian topoi or detailed questions, designate the context in which the transgression occurred very thoroughly and ‘actively participate’ in the confessional act, rather than simply recording it. Lille’s ‘hermeneutical’ approach to confession is also reflected in Robert Grosseteste’s (ca.1168–1253) De modo confitendi et paenitentias iniungendi, in which a moderate phronetic approach allows for the full discretion of the confessor, rather than following the rigid prescriptions of the Summae confessorum only. Secondly, William of Auvergne’s (ca.1180–1249) contribution to the interpretation of the Summae confessorum in his Poenitentia is indicated in his utilitarian ethics, in which the interests of the ethical ‘other’ is related to the confessing ‘self’: even though matrimony is for Auvergne the only realm where the other’s interests are not necessarily compromised by sexual contact, several considerations regarding ‘improper sex’, precisely within matrimony, apply according to the relevant penitential guidelines. Thirdly, Paul of Hungary’s (ca.1180–1241) De confessione is considered in terms of his reflections on ‘paying sexual debt’, and on the relation between regulated sexual release and the legitimacy of sexual gratification, again within the context of matrimony.Contribution: This article contributes to Foucault-scholarship by elucidating and expanding Foucault’s condensed reading of 13th-century confessional scripts in La volonté de savoir, with reference to the relevant texts of Alan of Lille (d.1203), William of Auvergne (ca.1180–1249) and Paul of Hungary (ca.1180–1241).